1995
DOI: 10.1023/a:1016208703380
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Two types of polyglycerol ester of fatty acid (PGEF)-based microspheres were prepared: Carbopol 934P (CP)-coated microspheres (CPC-microspheres) and CP-dispersion microspheres (CPD-microspheres). Comparative studies on mucoadhesion were done with these microspheres and PGEF-based microspheres without CP (PGEF-microspheres). In an in vitro adhesion test, the CPD-microspheres adhered strongly to mucosa prepared from rat stomach and small intestine because each CP particle in the CPD-microsphere was hydrated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(19 citation statements)
references
References 17 publications
0
18
0
1
Order By: Relevance
“…Macromolecules introduced via paracellular permeability can be increased by using polymeric materials such as chitosan, starch, or poly(acrylate). 109,110 The absorption of nanoparticles via the endocytotic pathway is either by receptor-mediated endocytosis ( i. e . active targeting) or by adsorptive endocytosis, where the ligands do not take part.…”
Section: Nanomedicine As An Emerging Therapeutic Approach For Real mentioning
confidence: 99%
“…Macromolecules introduced via paracellular permeability can be increased by using polymeric materials such as chitosan, starch, or poly(acrylate). 109,110 The absorption of nanoparticles via the endocytotic pathway is either by receptor-mediated endocytosis ( i. e . active targeting) or by adsorptive endocytosis, where the ligands do not take part.…”
Section: Nanomedicine As An Emerging Therapeutic Approach For Real mentioning
confidence: 99%
“…The general benefits of CP are high viscosity at low concentrations, thermal and microbiological resistance, and shelf life. Moreover, this polymer is capable of adhering to the surface of the object by forming functional groups (such as hydrogen bond) that has been used for the application in biological barrier , drug release profiles, buccal , nasal , and intestinal . For example, Garipova et al reported that absorption band is the formation of ionic bonds between carboxyl groups of CP and dimethylamino groups of a terpolymer of N,N‐dimethylaminoethyl methacrylate with methylmethacrylate and butylmethacrylate.…”
Section: Introductionmentioning
confidence: 99%
“…Various attempts have been made to prolong the residence time of the dosage forms within the stomach. [12] Prolongation of the gastric residence time (GRT) of delivery devices could be achieved by promoting adhesion to the mucous membranes,[3] which acted by preventing passage of the microspheres through the pylorus[4] or by maintaining them in a buoyant fashion in gastric juice. [5–7] With regard to the floating devices, Innuccelli et al ,[8–10] reported that an air-contained multiple-unit compartment system showed excellent buoyancy in vitro and prolonged GRT relative to the controls in vivo in the fed state.…”
Section: Introductionmentioning
confidence: 99%